Corporate Governance and Investment Efficiency: The Mediating Effect of Earnings Quality - Robert Jao; Fransiskus Randa; Anthony Holly; William Jose Sutadji (IECON: International Economics and Business Conference, 2023)
The purpose of this research was to investigate the effect of corporate governance on earnings quality, corporate governance and earnings quality on investment efficiency, and also the effect of corporate governance on investment efficiency mediated by earnings quality. The theory used in this research is agency theory. Population used is the whole manufacture company listed in Indonesia Stock Exchange period 2018-2020. This study uses secondary data which are financial statement and annual report that published by IDX and official company’s website. Sampling method used is purposive sampling method and obtained 42 companies for 3 years. The analytical method used is path analysis and hypothesis mediation analysed by using sobel test. The result of analysis shows that corporate governance has a positive and significant effect on earnings quality. Earnings quality have positive and significant effect on investment efficiency, corporate governance has a positive but not significant effect on investment efficiency. This research also shows that earnings quality plays a role in mediating the effect of corporate governance on investment efficiency which is fully mediation.